Sosialisme Islam Menurut Mustafa al-Siba‘i: Islamic Sosialisme According to Mustafa al-Siba‘i - Mohd Hatib Ismail; Ahmad Sunawari Long; Siti Rohani Jasni (RABBANICA - Journal of Revealed Knowledge, 2024)
The ideology of socialism has emerged among Western thinkers to create a society based on social justice. Mustafa al-Siba‘i, a Muslim thinker from Syria believed that the social justice emphasised in the concept of socialism is closely related to Islamic teachings, leading him to write a book titled ‘Islamic Socialism’. However, a question arose as to whether Mustafa al-Siba‘i’s ideas were acceptable and aligned with the core teachings of Islam, as derived from the Qur'an and the Sunnah. This study examines Mustafa al-Siba'i's intellectual background, which shaped his idea of Islamic socialism. It also compares Islamic socialism and Islamic society concepts. Data were collected by assembling Mustafa al-Siba‘i’s works on the social system and his ideas on socialism. The data were analysed using historical and content analysis methods based on his works. The findings revealed that Mustafa al-Siba‘i was an Islamic scholar committed to society and community. He introduced the idea of Islamic socialism to balance social justice, encompassing both individual and societal rights. His concept of Islamic socialism also does not conflict with the foundations and principles of Islamic teachings. Ideologi sosialisme lahir dalam kalangan pemikir Barat bagi mewujudkan sebuah masyarakat yang berteraskan keadilan sosial. Mustafa al-Siba‘i seorang pemikir muslim dari Syria juga berpandangan keadilan sosial yang ditekankan dalam konsep sosialisme sangat berkait rapat dengan ajaran Islam sehingga beliau menulis sebuah buku yang bertajuk ‘Sosialisme Islam’. Namun, Adakah idea-idea Mustafa al-Siba’i dapat diterima serta selaras dengan panduan al-Quran dan al-Sunnah? Kajian ini bertujuan untuk mengkaji latar belakang pemikiran Mustafa al-Siba‘i yang membentuk idea sosialisme Islam. Kajian ini juga akan menganalisis perbandingan pemikiran sosialisme Islam dengan konsep kemasyarakatan Islam. Pengumpulan data dijalankan dengan mengumpul karya Mustafa al-Siba‘i yang berkaitan sistem kemasyarakatan dan idea sosialisme beliau. Manakala, data akan dianalisis menggunakan kaedah analisis persejarahan dan analisis kandungan terhadap karya beliau. Hasil kajian menunjukkan bahawa Mustafa al-Siba‘i merupakan seorang sarjana Islam yang komited dalam bidang sosial dan kemasyarakatan. Beliau memperkenalkan idea sosialisme Islam untuk mengimbangi keadilan sosial yang meliputi hak-hak individu dan masyarakat. Idea sosialime Islam beliau juga tidak bertentangan dengan dasar dan prinsip ajaran Islam.